PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL EXPERIENTIAL LEARNING PADA MATERI PRISMA DAN LIMAS KELAS VIII SMP - Septianita, Devi; Suanto, Elfis; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the restrict of mathematics learning instruments as supporting learning referring to 2013 Curriculum. This research aimed to develop mathematics learning device that are syllabus, Lesson Plan (RPP), and Students Worksheet (LKPD) using experiential learning model on prism and pyramid of 8th grade.This type of this research is development research (R & D) using the 4D development procedure; define, design, develop and desseminate. The valid learning device then tested in two stages, the small group trial with subjects are 10 students of class VIII SMP Negeri 1 Pekanbaru and large group trial with subjects are 35 students of class VIIIHL SMP Negeri 1 Pekanbaru. Based on the data analysis and discussion can be concluded that the syllabus, RPP, and LKPD are valid with an average value for the syllabus is 3.84, the average value for the RPP is 3.73, and the average value for the LKPD is 3.58, and LKPD is practical to use by learners class VII with an average value for the small group trial is 98.75% and the average value for large group trial is 94.8%.Key Words: Learning Instruments, Experiential Learning Models, Validity and Practicality